A Robust Two-Step Process for the Efficient Conversion of Acidic Soybean Oil for Biodiesel Production - Ma, Gaojian; Dai, Lingmei; Liu, Dehua; Du, Wei (Catalysts, 2018)
Acidic oil, which is easily obtained and with lower cost, is a potential raw material for biodiesel production. Apart from containing large quantity of FFAs (free fatty acids), acidic oil usually contains some amount of inorganic acid, glycerides and some other complex components, leading to complicated effect on lipase’s catalytic performance. Exploring the efficient process of converting acidic oil for biodiesel production is of great significance to promote the use of acidic oil. A two-step conversion process for acidic soybean oil was proposed in this paper, where sulfuric acid-mediated hydrolysis was adopted first, then the hydrolyzed free fatty acid, collected from the upper oil layer was further subject to the second-step esterification catalyzed by immobilized lipase Novozym435. Through this novel process, the negative effect caused by harmful impurities and by-product glycerol on lipase was eliminated. A fatty acid methyl ester (FAME) yield of 95% could be obtained with the acid value decreased to 4 mgKOH/g from 188 mgKOH/g. There was no obvious loss in lipase’s activity and a FAME yield of 90% could be maintained with the lipase being repeatedly used for 10 batches. This process was found to have a good applicability to different acidic oils, indicating it has great prospect for converting low quality oil sources for biodiesel preparation.